VILJENS SVAGHED: Hamlet og Macbeth - Hastrup, Kirsten (Tidsskriftet Antropologi, 2007)
The concept of person derives from latin persona, originally referring to the ritual or dramatic mask. In classical Rome, the category came to include the juridical person, who – like other dramatis personae – had a particular position in society. In this article, an analysis of two well known characters in Shakespeare’s plays are used to rethink the conflation of the dramatic and social character in any person. By focussing on the idea of the will as an immanent feature of the modern person, it is shown how he or she is both cough caught up in a drama beyond control and contributing to its – unforeseen – course. In this sense the modern person is like Hamlet or Macbeth, whose destinies were partly a function of a larger unfolding drama, and partly of their own decisions to act upon and within it.